ANALYSIS OF STRUCTURAL EQUATION MODEL FACTORS AFFECTING THE PERFORMANCE OF THE ORCHID INDUSTRY FOR EXPORT - Somnam, Nettawan; Tonglim, Tongtang; Thurapaeng, Chertchai (Life Sciences and Environment Journal, 2022)
The purposes of this research were to (1) find out factors affecting the performance of orchid industry for export; (2) analyze the structural equation model affecting the performance of orchid industry for export. The samples were 300 entrepreneurs in the lower central region of Thailand which run a business of exporting orchids. Data were collected and analyzed using questionnaires, in-depth interview, descriptive statistic, content analysis and structural equation model. The result of the study revealed that (1) the importance of entrepreneur, marketing management, external environment, production management, and performance were at high levels with average score of 4.23, 4.61, 4.44, 4.40 and 4.46 respectively; (2) the structural equation model affecting the performance of orchid industry for from this research corresponded to the literature and empirical data (c2=406.597, df=160, GFI=0.939, RMR=0.047, RMSEA=0.038) which met the criteria set for the results of the causal influence analysis. When the total effect of the model was considered,it was found that the general external environment had the highest effect (TE=0.56), followed by Marketing Management (TE=0.51), Entrepreneurship (TE=0.34) and Manufacturing Management (TE=0.340).